Pseudo-octahedral nickel(ii) complexes of strongly absorbing benzannulated pincer-type amido ligands: ligand-based redox and non-Aufbau electronic behaviour. Issue 6 (18th January 2021) - Braun, Jason D.; Lozada, Issiah B.; Shepit, Michael; van Lierop, Johan; Herbert, David E.
Abstract : The synthesis, structures and electronic characterization of three strongly coloured, pseudo-octahedral Ni(ii ) complexes supported by redox-active diarylamido ligands featuring benzannulated N -heterocyclic donor arms are reported. Abstract : The synthesis, structures and electronic characterization of three strongly coloured, pseudo-octahedral Ni(ii ) complexes supported by redox-active diarylamido ligands featuring benzannulated N -heterocyclic donor arms are reported. The S = 1 paramagnets each present two singly occupied molecular orbitals (SOMOs) identified as metal-based by density functional theory (DFT), consistent with solid-state and solution magnetism measurements. Upon applying oxidative potentials, non-Aufbau behaviour leads to the appearance of intense and well-defined absorption features extending into the near IR (NIR). The attribution of these features to the onset of aminyl radical character through ligand-based redox is corroborated by exceptionally strong intervalence charge-transfer (IVCT) transitions ascribed to electronic communication between two Namido moieties across a Ni(ii ) bridge.